Предмет: Алгебра,
автор: Shark2120983
помогите пж кто может
Приложения:
Ответы
Автор ответа:
1
Ответ:
286. 72; 288. 1.
Объяснение:
286.
(2х + 3у)² + 4х · (2х - 3у) = 4х² + 12ху + 9у² + 8х² - 12ху = 12х² + 9у²
при х = √3 и у = 2 получим
12 · 3 + 9 · 4 = 36 + 36 = 72
288.
у(5у + 2х) - (х + у)² = 5у² + 2ху - х² - 2ху - у² = 4у² - х²
при х = √11 и у = √3 получаем
4 · 3 - 11 = 1
Похожие вопросы
Предмет: Геометрия,
автор: kihvika91
Предмет: Русский язык,
автор: kserik003
Предмет: Українська мова,
автор: svetavasilcenko14
Предмет: Обществознание,
автор: DanSNAKe
Предмет: Химия,
автор: sasha228822